Resistance training beyond momentary failure: the effects of past-failure partials on muscle hypertrophy in the gastrocnemius - Larsen, Stian; Swinton, Paul Alan; Sandberg, Nordis Østerås; Kristiansen, Benjamin Sandvik; Fredriksen, Andrea Bao; Falch, Hallvard Nygaard; van den Tillaar, Roland; Wolf, Milo (Frontiers in Psychology, 2025)
Muscle hypertrophy is often a desired goal of resistance training, and strategies that extend training beyond momentary failure may enhance muscular adaptations. Thus, the objective of this study was to assess whether performing additional past-failure partial repetitions beyond momentary failure increased muscle hypertrophy. A total of 23 untrained men completed a 10-week within-participant intervention study. This study comprised two weekly resistance training sessions of four sets of standing Smith machine calf raises. One limb was randomly allocated to the control condition performing sets to momentary failure (PLANTARMF), and the other limb was allocated to the test intervention that included additional past-failure partial repetitions in the lengthened position (DORSIvf). Muscle thickness of the medial gastrocnemius muscle was measured both pre- and post-intervention via ultrasound. Data were analysed within a Bayesian framework using a mixed-effect model with random effects to account for the within-participant design. The average treatment effect (ATE) was measured to assess any difference in condition and inferences made based on the ATE posterior distribution and associated Bayes Factor (BF). The main findings were that the PLANTARMF and DORSIVF legs increased medial gastrocnemius hypertrophy by 6.7 and +9.6%, respectively. The results identified an ATE favouring the inclusion of additional partial repetitions (0.62 [95%CrI: 0.21–1.0 mm; p(>0) = 0.998]) with ‘strong’ evidence (BF = 13.3) supporting a priori hypothesis. Therefore, when the goal is to train for maximum gastrocnemius hypertrophy over a relatively short time period, we suggest performing sets beyond momentary failure as a likely superior option.